Territorial Governance Rehabilitation of Old Cities: Taza City Example - Jaouad, El-bazoui; Chouitar, Mohamed; Bouberria, Abdelouaed (Journal of Humanities & Social Sciences, 2020)
The reality of historical cities of Morocco today .which is reflected in the fading and deterioration of its built framework and the loss of many of its social and economic functions has prompted many actors in the field of cultural and historical heritage to take a series of measures in order to rehabilitate them to cope with the pace of development, witnessed by its urban and social surrounding.In this context, the city of Taza is one of the ancient Moroccan cities that have a glorious history, an integrated urban fabric, and unique historical monuments. it is an essential building block of Morocco’s cultural heritage, which has played its part throughout history and withstood all the challenges it has faced.However; despite its importance the city has not received the attention it deserves for its historical value, its historical monuments are currently suffering from the continuous deterioration and fading, which necessitates the search for an effective strategy that evokes the criteria of governance as a gateway to the rehabilitation of its ancient heritage.To address this issue we will try to answer the following questions:To what extent is the territorial governance a mechanism for the rehabilitation and development of the ancient city of Taza?What are the most important rehabilitation projects of the ancient city of Taza?
Keywords: the ancient city; territorial governance; heritage; rehabilitation; ancient textiles